Homogenization of optimal control problems with state constraints of inequality type - Dekun, N. O. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Problem of homogenization of optimal control problem with the state constraints of inequality type for kvazilinear equation of elliptic type is investigated. Assuming that all the components of mathematical description of the given problem depend on a small parameter, its asymptotic behavior is studied and mathematical model of limit (homogenized) optimal control problem and its variation properties are investigated.